(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Dielectric properties of EMA,MMA&BMA with AMPS in composition (50/50) have been studied over frequency range from 100Hz to 100kHz and temperature range from room temperature to 180oC.The Copolymers characterized by DSC. The frequency dependence of the dielectric constant and dielectric loss has been investigated. Dielectric constant decreases with increasing frequency and increases with temperature. AC Conductivity calculated and data were analyzed. The AC Conductivity increases with increasing temperature and frequency. The present report deals with a systematic study of dielectric property of EMA,MMA&BMA with AMPS as a function of both frequency and temperature.